The Dilemma of War and Peace in the Trend of the XXI Century (Russian – Ukrainian case) - Perepelytsia, Hryhorii (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2021)
In the presented article the author asks how the essence of the relationship between such states of international relations as war and peace has changed under the influence of the trends of the XXI century. A clear empirical example for such an analysis was the modern Russian-Ukrainian war, a manifestation of which we see on the Donbass. This war was largely the result and manifestation of these new trends in international relations at both the regional and global levels. First of all, these trends and their destructive consequences are typical for the security sphere. From so the dilemma of war and peace takes on a new dimension and becomes one of the most pressing problems of the theory of war and peace and the theory of international relations. The purpose of this article is to understand how the essence of the relationship between such states of international relations as war and peace has changed under the influence of the 21st century trends. In order to properly investigate this problem, was chosen as an object, a striking manifestation of which we see on the Donbass. Research questions relate to changing approaches to understanding the dilemma of war and peace and the nature of the relationship between these states of international relations under the influence of the 21st century trends. To address this research challenge, a systematic review of contemporary research on various aspects of war and peace has been carried out. The answers are based on a study of the criteria for determining the state of war and peace and the determinants that influence the dynamics of change in these states. The study used deductive methods, comparative, political and conflict analysis, as well as neo-realistic and neoliberal approaches to treating the dilemma of war and peace. The article based on the assumption that the modern Russo-Ukrainian war became a consequence and manifestation of these new trends in international relations both at the regional and global levels. The conclusions drawn from this study require a conceptual rethinking and a new reading of the dilemma of war and peace, which are becoming hybrid. Therefore, understanding the new quality of these hybrid forms of war and peace is a very important and necessary task. To solve it, it is necessary to determine how the parameters of the relationship between peace and war have changed. Empirical observations show that one of the new features of this relationship is the blurring of the boundaries of war and peace. The objectives of the study are based on the discovery of a new content of the categories of war and peace and their interdependence due to the influence of 21st century trends in the modern system of international relations. The results of the study are based on the analysis of modern research on various aspects of the war and peace, as well as empirical data on the course of the Russian-Ukrainian war. This article provides an overview of current research on various aspects of war and peace, identifies the interrelationships, interdependencies, and boundaries between hybrid warfare and hybrid peace. The author tried to define the criteria for such a distinction between war and peace, based on the neoliberal and neorealist theory of international relations. The scientific novelty of this publication is that the author clarified the methodological reasons for the unresolved dilemma of war and peace in the current trends of the 21st century. The article concludes with a forecast of the consequences of the unresolved dilemma of war and peace for national and international security. Recommendations are given for a possible solution to the problem of war and peace on Donbass. The research presented in this article is an attempt to conceptually rethink and re-read the dilemmas of war and peace that are becoming hybrid. The article greatly expands the understanding of how the parameters of the relationship between peace and war have changed.

W prezentowanym artykule autor pyta, w jaki sposób istota relacji między takimi państwami stosunków międzynarodowych, jak wojna i pokój, zmieniła się pod wpływem trendów XXI wieku. Wyraźnym empirycznym przykładem takiej analizy była współczesna wojna rosyjsko-ukraińska, której żywy przejaw obserwujemy w Donbasie. Ta wojna była w dużej mierze wynikiem i przejawem tych nowych trendów w stosunkach międzynarodowych zarówno na poziomie regionalnym, jak i globalnym. Przede wszystkim te trendy i ich destrukcyjne konsekwencje są typowe dla sfery bezpieczeństwa. Stąd dylemat wojny i pokoju nabiera nowego wymiaru i staje się jednym z najbardziej palących problemów teorii wojny i pokoju oraz teorii stosunków międzynarodowych. Celem artykułu jest zrozumienie, jak istota relacji między takimi państwami stosunków międzynarodowych, jak wojna i pokój, zmieniła się pod wpływem trendów XXI wieku. Aby właściwie zbadać ten problem, wybrano obiekt, którego uderzającą manifestację widzimy na Donbasie. Pytania badawcze dotyczą zmieniającego się podejścia do rozumienia dylematu wojny i pokoju oraz natury relacji między tymi stanami stosunków międzynarodowych pod wpływem trendów XXI wieku. Aby sprostać temu wyzwaniu badawczemu, przeprowadzono systematyczny przegląd współczesnych badań dotyczących różnych aspektów wojny i pokoju. Odpowiedzi opierają się na badaniu kryteriów określania stanu wojny i pokoju oraz uwarunkowań wpływających na dynamikę zmian w tych państwach. W badaniu wykorzystano metody dedukcyjne, analizę porównawczą, analizę polityczną i konfliktową, a także podejście neorealistyczne i neoliberalne do rozwiązywania dylematu wojny i pokoju. Artykuł opierał się na założeniu, że współczesna wojna rosyjsko-ukraińska stała się konsekwencją i manifestacją tych nowych trendów w stosunkach międzynarodowych zarówno na poziomie regionalnym, jak i globalnym. Wnioski wyciągnięte z tego badania wymagają przemyślenia konceptualnego i nowego odczytania dylematu wojny i pokoju, które stają się hybrydami. Dlatego zrozumienie nowej jakości tych hybrydowych form wojny i pokoju jest bardzo ważnym i koniecznym zadaniem. Aby go rozwiązać, konieczne jest ustalenie, jak zmieniły się parametry relacji między pokojem a wojną. Z obserwacji empirycznych wynika, że jedną z nowych cech tej relacji jest zacieranie się granic wojny i pokoju. Cele badania opierają się na odkryciu nowej treści kategorii wojny i pokoju oraz ich współzależności w wyniku wpływu trendów XXI wieku na współczesny system stosunków międzynarodowych. Wyniki pracy opierają się na analizie współczesnych badań dotyczących różnych aspektów wojny i pokoju, a także danych empirycznych dotyczących przebiegu wojny rosyjsko-ukraińskiej. Ten artykuł zawiera przegląd aktualnych badań dotyczących różnych aspektów wojny i pokoju, identyfikuje współzależności i granice między wojną hybrydową a pokojem hybrydowym. Autor próbował zdefiniować kryteria takiego rozróżnienia między wojną a pokojem w oparciu o neoliberalną i neorealistyczną teorię stosunków międzynarodowych. Nowością naukową tej publikacji jest wyjaśnienie przez autora metodologicznych przyczyn nierozwiązanego dylematu wojny i pokoju w obecnych trendach XXI wieku. Artykuł kończy się prognozą konsekwencji nierozwiązanego dylematu wojny i pokoju dla bezpieczeństwa narodowego i międzynarodowego. Podaje się zalecenia dotyczące możliwego rozwiązania problemu wojny i pokoju w Donbasie. Badania przedstawione w tym artykule są próbą konceptualnego przemyślenia i ponownego odczytania dylematów wojny i pokoju, które stają się hybrydami. Artykuł znacznie poszerza wiedzę o tym, jak zmieniły się parametry relacji między pokojem a wojną.
Dylemat wojny i pokoju w trendach XXI wieku (przypadek rosyjski – ukraiński)
Keywords: war; peace; conflict; dilemma; Donbas; wojna; pokój; konflikt; dylemat; Donbas